Assessing the impact on pharmacists' time by introducing a technician screening process for clinical trial prescriptions. (26th March 2021) - Mistry, D; Awan, S; Lundy, E; Bedford, C; Thorp, H; Houseman, K; Chapman, J; Smalley, P; Stradling, J
Abstract: Introduction: Various national guidance from the Lord Carter 2016 report to the NHS Long term plan have emphasised the need to transform traditional hospital pharmacy and make work streams more efficient. [1] A clinical trials pharmacist has historically validated clinical trial medicines. Whilst this is good practice for non-chemotherapy prescriptions, it is not a requirement of the Clinical Trial Regulations. [2] Interruption to validate trial prescriptions can have a negative impact on pharmacists' duty and consequently patient outcomes. With limited data available, this issue has been highlighted by anecdotal evidence. Due to the often complex requirements associated with trials, the research team are responsible for assessing the suitability of treatment. This includes checking interactions with concomitant medication, reviewing blood results and patient counselling. The clinical aspect of the pharmacist validation is therefore removed, allowing technicians to be involved in the screening of suitable prescriptions. Much is written on technicians extending their roles in the clinical setting, but this service improvement focuses on enhancing their role within the pharmacy clinical trials department. Aim: To evaluate the amount of pharmacists' time saved by the introduction of technician screening of clinical trial prescriptions. Method: A risk-based proforma was created and used by a pharmacist to assess clinical trial prescriptions for the suitability of screening by a Band 7 technician. Only prescriptions with pre-printed doses, no aseptic preparation or additional medicines, were approved for technician screening. The process of screening therefore only involves the checking of patient and prescriber details, allergy status and possibly a medication randomisation. The technicians under-went an in-house training including the screening of prescriptions under pharmacist supervision. A quantitative data collection tool was used to review the screening / validation of all nonchemotherapy clinical trial prescriptions received at two sites over a two-week period in September 2020. The data collection tool was piloted and all data was analysed using Microsoft Excel. Results: A total of 89 prescriptions were received. 56 (63%) were eligible for technician screening, of which a suitable technician validated 50%. Across both sites a total time of 360 minutes were spent validating/screening prescriptions including solving prescription related issues. Combining the time taken by a pharmacist to return from a clinical area and screening time consequently saved a total of 227 minutes of pharmacists' time. Conclusion: Distributing the workload amongst trained staff saves pharmacist's time, which can be utilised on clinical and complex tasks. This does not eliminate the requirement of a pharmacist to validate prescriptions however; it reduces the frequency and streamlines the service. Further data collection is required to analyse the direct impact on patients' and any changes in the number of reported errors. A limitation to the study is the lack of data prior to implementation as a comparator. Additionally, during data collection there were no suitable technicians available at one site due to the Covid-19 pandemic, resulting in only 50% of eligible prescriptions being screened by a technician. Ultimately, this does not change the outcome; enhancing technician's roles allows pharmacists' time to be used more efficiently. References: 1. Royal Pharmaceutical Society. Shaping Pharmacy for the future. Hospital Pharmacy: A briefing for members in England. 2017. Available at: https://www.rpharms.com/Portals/0/Hospital%20pharmacy%20briefing%20-%20final.pdf [Accessed: 11/10/20] 2. National Pharmacy Clinical Trials Advisory Group. Professional Guidance on Pharmacy Services for Clinical Trials v2.1. 2019. Available at: https://www.rpharms.com/Portals/0/RPS%20document%20library/Open%20access/Hospital%20Pharmacy%20Hub/Practice_Guidance_on_Pharmacy_Services_for_Clinical_Trials_v2.1.pdf?ver=2020-09-18-095937-733 [Accessed: 09/10/20]